Classification of skin involvement in levamisole-adulterated cocaine induced vasculopathy (2018)
ABSTRACT: Background Up to 88% of cocaine is tainted with levamisole, an anthelmintic withdrawn from the market due to toxicity. Since 2010 levamisole-adulterated cocaine induced vasculopathy (LACIV) patients, characterised by retiform purpura, ear necrosis, multisystemic compromise and positivity for multiple autoantibodies, have been reported. Knowing the pattern and the severity of skin involvement is essential in the approach of these patients. Objectives To describe the cutaneous manifestations of patients with LACIV and to propose a classification of skin involvement. Methods We describe the skin compromise of 30 patients with LACIV evaluated between December 2010 and May 2017. Based on this series and the review of the literature, we propose a classification according to the distribution and severity of the lesions. Results All patients were mestizo, median age of 31 (IQR 27–38), male:female ratio 5:1, time from symptoms to diagnosis 12 months (IQR 6–24). The most frequent clinical manifestations were skin lesions: ear necrosis (73%) and retiform purpura (83%) affecting the extensor part of the limbs, buttocks, face, and abdomen; sparing the scalp, palms and soles. Retiform purpura was classified in four grades according to distribution and severity (image). Skin biopsies revealed leukocytoclastic vasculitis (24%), pseudo-vasculitis (19%), thrombotic vasculopathy with leukocytoclastic vasculitis (19%), thrombotic vasculopathy with pseudo-vasculitis (19%), and pyoderma gangrenosum with vasculopathy (5%).